Powder X-ray structural analysis and bandgap measurements for (CaxSr2−x)MnWO6 (x = 0.25, 0.5, 0.75, 1.5, 1.75). Issue 3 (September 2022) - Wong-Ng, Winnie; Yang, Yuqi; Lan, YuCheng; Liu, Guangyao; Kafle, Amrit; Liu, Weifang; Hou, Jie; Windover, Donald; Huang, Qing; Krylyuk, Sergiy; Kaduk, James A.
Abstract : The structure, powder diffraction patterns and bandgap measurements of a series of manganese- and tungsten-containing alkaline-earth double perovskites (Ca x Sr2− x )MnWO6 ( x = 0.25, 0.5, 0.75, 1.5, 1.75) have been investigated. Powder X-ray diffraction patterns of this series of compounds measured at room temperature have been submitted to be included in the Powder Diffraction File (PDF). These compounds crystallize in monoclinic space group P 21 / n (No.14). From (Ca1.75 Sr0.25 )MnWO6 to (Ca0.25 Sr1.75 )MnWO6, lattice parameters a range from 5.6729(2) Å to 5.6774(4) Å, b from 5.5160(2) Å to 5.6638(4) Å, c from 7.8741(3) Å to 8.0051(4) Å, V from 240.39(2) Å 3 to 257.410(12) Å 3, and Z = 2. These compounds are pseudo-tetragonal. They all consist of distorted MnO6 and WO6 octahedra with rotational mismatch angles and tilt angles with respect to each other. For (Ca x Sr2− x )MnWO6, as x increases, the mismatch angles for MnO6 octahedra increase from 7.96 (6)° to 13.12(8)° and from 9.28(7)° to 14.87(9)° for WO6 octahedra. Correspondingly, the tilt angles range from 11.60(15)° to 14.20(3)° for MnO6, and from 13.34(2)° to 16.35(3)° for WO6 . Bandgap measurements suggest that these compounds to be direct-allowed semiconductors with bandgaps ranging from 1.5 to 2.5 eV, indicating that members of (Ca x Sr2− x )MnWO6 are potential photocatalysts and photovoltaic materials that absorb visible light of the solar spectrum.